Strategi Pondok Pesantren Al-Manar Muhammadiyah Pengasih Putri dalam Meningkatkan Hafalan Al-Qur’an Santri - Nasiroh, Hikmatun (YASIN, 2024)
Islamic boarding schools have an important role in Islamic religious education, especially in memorizing the Koran. However, the strategies applied often varies in improving students' memorization results. Therefore, this research aims to find the strategies implemented by the Al-Manar Muhammadiyah Pengasih Putri Islamic boarding school in improving students' memorization. The method used in this research is a qualitative approach with descriptive research and case studies. Data collection techniques used include interviews, observation and document analysis. The data that has been collected is then analyzed thoroughly to understand the Islamic boarding school's strategy in improving and memorizing the Al-Quran at the Al-Manar Muhammadiyah Pengasih Putri Islamic Boarding School. The results of this research are the strategies used by the Al-Manar Muhammadiyah Pengasih Putri Islamic boarding school in improving students' memorization, namely grouping students according to their memorization ability, giving monthly reminders, making monthly memorization targets, making a suitable takhfidz schedule between pilgrimage and muraja'ah, playing mutal every morning and evening, murajaah, tasmi' and the juz increase exam (UKJ). The results of implementing the strategies above show that the students of the Al-Manar Muhammadiyah Pengasih Putri Islamic Boarding School experienced significant changes where the students' memorization increased.